First evidence of a therapeutic effect of miransertib in a teenager with Proteus syndrome and ovarian carcinoma. Issue 7 (6th May 2019) - Leoni, Chiara; Gullo, Giuseppe; Resta, Nicoletta; Fagotti, Anna; Onesimo, Roberta; Schwartz, Brian; Kazakin, Julia; Abbadessa, Giovanni; Crown, John; Collins, Conor D.; Ranieri, Carlotta; Scambia, Giovanni; et al.
Abstract: Proteus syndrome (PS) is an ultra‐rare disease characterized by progressive, disproportionate, segmental overgrowth caused by a somatic gain‐of‐function mutation p.Glu17Lys in the oncogene AKT1 . The disease has high morbidity and mortality rates due to the increased risk for patients to develop cancer and progressive overgrowth. A teenage patient with severe PS phenotype developed a pelvic recurrence of low‐grade serous ovarian carcinoma (LGSOC). Taking into consideration, recent results of the use of AKT inhibitors both in PS and AKT‐mutant cancers, we treated the patient on a compassionate basis, with miransertib (ARQ 092), a potent, selective, allosteric AKT inhibitor. Targeted deep sequencing assay of PI3K/AKT pathway genes of the affected overgrowth lesion (cerebriform connective tissue nevus) and the tumor tissues detected the same activating AKT1 mutation in both. Treatment with miransertib led to a complete remission of the cancer and a significant improvement in the patients' everyday life. The treatment is still ongoing at 22 months. This is the first report showing the therapeutic effects of an AKT inhibitor on both benign and malignant tissues that harbor the same pathogenic AKT1 mutation. The present article showed that personalized medicine is feasible in ultra‐rare diseases.